GAMBARAN STATUS ANEMIA PADA REMAJA PUTRI DI WILAYAH PEGUNUNGAN DAN PESISIR PANTAI (Studi di SMP Negeri Kecamatan Getasan dan Semarang Barat) - Ghea Yanna Aulia; Ari Udiyono; Lintang Dian Saraswati; Mateus Sakundarno Adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Anemia is a condition in which the hemoglobin level is less than expected according to age and gender. Anemia is one of the health problems in Indonesia. Based on data from Riskesdas 2013 there were 21.7% of the population with a hemoglobin level less than the normal limit to the proportion of 20.6% in urban and 22.8% rural and 18.4% men and 23.9 % of women. By age group, 28.1% in infants with hemoglobin levels less than 11.0 g / dL, children aged 5-14 years (Hb less than 12.0 g / dL) by 26.4%, of children ages 15-24 (Hb less than 12.0 g / dL) 18.4%, and 37.1% in pregnant womenThe aim of the study is to analyze differences in some risk factors foranemia on female teenagers in highland and coastal areas. The study is anobservational study which uses cross sectional approach. Population of the study are female middle school students class VII and VIII SMP Negeri in district Getasan and SMP Negeri in Semarang Barat Kota Semarang consisted of 100 respondents for each district.Prevalence of anemia in highland area is 58% while coastal area is 56%.